Essays in econometrics : collected papers of Clive W.J. Granger - Granger, C. W. J. (Clive William John), 1934-2009 (Econometric Society monographs, 2001)
These essays by Clive W.J. Granger span more than four decades and cover major topics in spectral analysis, seasonality, nonlinearity, methodology, and forecasting. The introduction by Eric Gysels, Norman R. Swanson and Mark W. Watson places the essays in context and demonstrates their enduring value.